(untitled) (PerCursos, 2007)
Este texto é uma reflexão sobre o papel de Oswaldo Rodrigues Cabral como intelectual atuante em Santa Catarina. Médico, publicista, professor, Cabral não se nega a discutir a complexidade cultural que aos seus olhos se apresenta. Além de médico e professor, foi deputado estadual e marcou presença como membro do Instituto Histórico e Geográfico de Santa Catarina e da Academia Catarinense de Letras. Discute-se, aqui,o pronunciamento feito por Cabral, em julho de 1939 no IHGSC intitulado “A República Juliana e as comemorações do seu centenário”. Palavras-chave: Identidade cultural. Comemorações. Políticas culturais.Abstract: This paper reflects on the role played by Rodrigues Cabral as an active intellectual in Santa Catarina. Being a medical doctor, a publicist, and a teacher, Cabral is keen on discussing the cultural complexity that surrounds him. In addition to being a doctor and a teacher, he was a state deputy, and was an active member of the Instituto Histórico e Geográfico de Santa Catarina (IHGSC – Geographic and Historic Institute of Santa Catarina) and the Academia Catarinense de Letras (Academy of Letters of Santa Catarina), to mention just part of his connections. The speech given by Cabral, in July 1939, at IHGSC, is discussed here. This speech received the title “The República Juliana and the celebrations of its centenary” Key Words: Cultural identity. Celebrations. Cultural policies.